A survey of 0 + 5 vascular surgery residency candidates: Perceptions of an applicant pool. (December 2016) - Lajos, Paul; Negrete, Alejandro; Ravin, Reid; Marin, Michael; Faries, Peter
Background: Applications to integrated (0 + 5) vascular surgery residencies have increased, while total applications have stayed relatively constant. This survey sought to document the perceptions of 0 + 5 vascular surgery applicants. Methods: Academic faculty conducted interviews for 0 + 5 residency match at an academic medical center in preparation for the National Resident Matching Program (NRMP) Main Residency Match. Applicant pool (n = 20) perceptions were determined with surveys. Participation was anonymous and voluntary. Results: Nineteen interviewees (26.3% female: 73.7% male), age (26.8 ± 2.6 years) responded (95% response rate). Of 19 respondents, 68% became interested in vascular surgery in their third year with 53% becoming aware of 0 + 5 programs in their third year. All respondents identified a vascular surgery attending at their institution as significant mentors. Forty-seven percent identified their mentor during their third year of medical school. All respondents felt that 0 + 5 training would prepare them adequately for the workforce and board certification exams. Almost all (89%) had plans to seek jobs immediately upon completion of residency. Conclusion: Applicants remained positive about their planned training and career paths. Attending vascular surgeons were identified as the strongest mentors, yet most students decided only in their third and fourth years to pursue 0 + 5 residencies. Educational debt remains a concern, and there may be consideration for a concerted effort to recruit potential candidates sooner.